Stability of soybean yield through different sowing periods - Lima, Wilmar Ferreira; Toledo, José Francisco Ferraz de; Arias, Carlos Alberto Arrabal; Oliveira, Marcelo Fernandes de (Pesquisa Agropecuaria Brasileira, 2000)
Soybean yield is highly affected by sowing period and there are significant productivity losses when sowings are done outward a relatively restricted period in many regions of Brazil. Breeding cultivars less sensitive to photoperiod and to temperature variations is desirable for adaptation to wider sowing period and wider latitude range and also make irrigated soybean cultivation possible during the fall-winter seasons in frost free regions. The possibility of selecting high yielding and stable lines for yield during various sowing periods was studied by analyzing the behavior of 100 non-selected advanced lines (F9 and F10), from each one of all possible biparental crosses involving the genotypes BR85-29009, OCEPAR 8, FT-2, and BR-13. Experiments were set up in a completely randomized design with single-plant hill plots and received supplementary irrigation. Sowing was on Sept 27, Oct 20, Nov 17, and Dec 17 in 1993/94 and Sept 20, Oct 20, Nov 17, and Dec 14 in 1994/95 at Londrina, PR, Brazil. Procedures of regression analysis and minimum variance among planting date means were efficient for selecting stable lines during the four sowing seasons. It was possible to select stable and high yielding genotypes through the four sowing periods in all the crosses. No specific cross was clearly better to produce a greater number of stable genotypes.